Organoleptic quality and shelf-life of dry noodle from maize flour and fish hydrolysate protein (Mizepi) for emergency food - Resti, Nina; Ayustaningwarno , Fitriyono; Anjani, Gemala; Syauqy, Ahmad; Nuryanto, Nuryanto; Chasanah, Ekowati; Purwani, Endang Yuli; Afifah, Diana Nur (Hasanuddin University Food Science and Technology Study Program, 2025)
Natural disasters have crucial impacts on food aspects. This problem can be addressed by innovations in nutrient-dense products. However, the reality is that innovation in emergency food products is still minimal, especially in those with high protein content. This research created Mizepi products made from maize flour and Fish Protein Hydrolysate (FPH) for existing emergency food requirements. This organoleptic quality research was conducted on 112 consumer panelists with seven formulations of Mizepi and compared them with maize flour and FPH in grams such as F1 (1:1), F2 (4:7), F3 (4:11), F4 (7:4), F5 (7:11), F6 (11:4), and F7 (11:7) using the Hedonic Test and Just About Right (JAR) on nine scales. Selection of the best formulation was analyzed using the Effectiveness Index Test method. The shelf life test was carried out on the best formulation, namely F4 using the Accelerated Shelf-Life Testing (ASLT) method at temperatures of 35 oC, 45 oC and 50 oC respectively. Samples were observed every 7 days for 28 days. Parameters using water content and Free Fatty Acid (FFA). The organoleptic quality test with hedonic test explained that the product with the most preferred categories is in terms of aroma (F6), color (F1), texture (F4), flavor (F6 and F4), and overall (F4). The most favorable JAR test results for color of all samples were the same, namely yellow, savoriness (F4 and F6), typical savory aroma of corn (F5, F6, F7), typical savory aroma of fish (F3), and crunchy texture (F4). Test results for the shelf life of Mizepi products in the best formulation can be stored well for 46 days at a temperature of 35 oC with water content parameters. The best formulation of F4 meets emergency food requirements, namely it is acceptable in terms of taste, and acceptable.